The Impact of Information Management Systems on the Performance of Commercial Banks in Nigeria - Chukwuedozie N. Ezema; Ernest O. Nonum; Chukwuebuka N. Umezinwa; Uche Anakwenze (Archives of Current Research International, 2018)
This study assessed the impact of Information and Communication Technology (ICT) on the performance of commercial banks in Nigeria for the period 1991 to 2012 using data sourced from 11 sampled commercial banks in Onitsha, Anambra State. This study applied Ordinary Least Square approach econometric techniques, Fixed and Random Effects Models in its analysis to ascertain the relationship between Banks Performance and the Application of ICT. The results indicate that Random Effects Model was appropriate. Also the findings reveal that the use of ICT in Nigerian banking industry increased return on equity. The regression and factor analysis showed that an insignificant size of profit exist without the introduction of ICT implying that ICT has a positive effect on profitability. Furthermore, the findings indicate strong relationship between sustained investment in ICT and efficiency. The study recommends among other things the enforcement of more policies that will boost proficient/appropriate utilization of ICT equipment rather than additional investments.